The Implementation of Story Jumper in Teaching Writing Descriptive Text - Meli Kamelawati; Lilis Suryani; Silpia Rahayu (IKIP Siliwangi, 2026)
Writing is one of the most essential yet challenging skills for elementary students, particularly in producing descriptive texts. Many learners struggle with vocabulary, sentence construction, and idea development, highlighting the need for effective instructional media. This study aimed to examine the effectiveness of StoryJumper in improving students’ descriptive writing skills, describe its classroom implementation, and identify students’ difficulties. The research employed a mixed-methods explanatory sequential design and involved 25 fifth-grade students at Tridaya Tunas Bangsa Elementary School, Cimahi. Data were collected through pre-tests, post-tests, observations, questionnaires, and interviews. Quantitative data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test with IBM SPSS 26. The results showed that both pre-test (Sig. = 0.113) and post-test (Sig. = 0.052) scores were normally distributed. The paired-sample t-test revealed a significant difference between pre-test and post-test scores (mean difference = -10.60, p < .05), indicating that StoryJumper effectively improved students’ descriptive writing skills. Qualitative findings showed increased student engagement, better idea development, and improved use of descriptive language. Despite these improvements, students still experienced difficulties with vocabulary, grammar, and confidence. Overall, StoryJumper proved to be an effective and engaging medium for teaching descriptive writing.